2009
DOI: 10.1038/modpathol.2009.40
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-3 expression in clear cell adenocarcinoma of the ovary

Abstract: Glypican-3 is a heparan sulfate proteoglycan that is overexpressed in various neoplasms such as hepatocellular carcinoma, malignant melanoma, and testicular yolk sac tumor. Glypican-3 is currently regarded as a tumor marker and potential target for immunotherapy. To clarify the significance of glypican-3 expression in ovarian clear cell adenocarcinoma, we evaluated glypican-3 expression by immunohistochemistry in nonneoplastic and neoplastic ovaries, and other Mü llerian duct derivatives including endometrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 36 publications
1
62
1
Order By: Relevance
“…32,33 However, one study reported HNF1b positivity in the nuclei of normal and tumor cells in the endometrium, 34 and the establishment of other markers may also be useful for differential diagnosis of clear cell adenocarcinoma. Annexin-A4, 35,36 HOXA10, 37 phospho-serine aminotransferase, 36 and glypican 3 38 are all suitable candidates. A recent study has shown that a certain proportion of papillary serous adenocarcinoma also exhibits Annexin-A4 expression related to chemoresistance, 39 and the expression of HOXA10 or glypican 3 is less frequently associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,33 However, one study reported HNF1b positivity in the nuclei of normal and tumor cells in the endometrium, 34 and the establishment of other markers may also be useful for differential diagnosis of clear cell adenocarcinoma. Annexin-A4, 35,36 HOXA10, 37 phospho-serine aminotransferase, 36 and glypican 3 38 are all suitable candidates. A recent study has shown that a certain proportion of papillary serous adenocarcinoma also exhibits Annexin-A4 expression related to chemoresistance, 39 and the expression of HOXA10 or glypican 3 is less frequently associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that a certain proportion of papillary serous adenocarcinoma also exhibits Annexin-A4 expression related to chemoresistance, 39 and the expression of HOXA10 or glypican 3 is less frequently associated with poor outcome. 37,38,40 Glypican 3 is also known to be expressed in yolk sac tumors of the ovary. 38 In this study, all of the 93 primary ovarian surface epithelial tumors that were not of the clear cell subtype and three cases of yolk sac tumors were all negative for napsin A staining, with the exception of focal (o10% area) staining of serous and endometrioid adenocarcinoma cases with clear cell-or hob-nail changes resembling clear cell adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…167,184,185 GP-3 positive staining in yolk sac tumor and negative staining in embryonal carcinoma is used as an additional marker in differentiating these 2 tumors. [186][187][188] It should be noted that GP-3 stains positively in choriocarcinoma and metastatic hepatocellular carcinoma and may be expressed in immature teratoma, metastatic acinar carcinoma of the pancreas, and squamous cell carcinoma of the cervix.…”
Section: Germ Cell Tumors Of the Ovarymentioning
confidence: 99%
“…GPC3 was expressed in about 40% of clear cell carcinomas (Maeda et al 2009;Umezu et al 2010) but rare in other types such as mucinous, endometrioid, or serous (Maeda et al 2009). One study showed that glypican-3 was significantly associated with poor overall survival in stage III/IV clear cell adenocarcinoma cases (Maeda et al 2009), whereas another study showed association with poor progression-free survival in stage I clear cell carcinoma patients (Umezu et al 2010). Both studies showed no correlations between its expression and clinicopathological factors (Maeda et al 2009;Umezu et al 2010).…”
Section: Glypicans In Breast and Ovarian Cancersmentioning
confidence: 99%